1986
DOI: 10.1111/j.1745-6584.1986.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐Water Recharge and Its Effects on Nitrate Concentration Beneath a Manured Field Site in Pennsylvania

Abstract: Ground‐water recharge to a shallow, unconfined, fractured dolomite aquifer underlying agricultural land in Lancaster County, Pennsylvania occurs by two mechanisms. Direct recharge occurs through pathways such as near‐surface bedrock fractures and sinkholes, and affects dissolved nitrate concentration of ground water within two to three days; its effects last only about one week. Gradual recharge occurs through small channels and pores in the unsaturated zone and affects dissolved nitrate concentration for seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Additionally, the unsaturated zone is thinner and probably more permeable at the Coastal Plain site than at the Piedmont site, and flow velocities in the zone probably are faster and traveltimes shorter. For comparison, faster recharge than that found at either of the sites for this study was observed throughout the year in an agricultural area underlain by a karst flow system in Pennsylvania (Gerhart, 1986;Hall, 1992b), where water percolates through sinkholes and bedrock fractures enlarged by solution weathering. Storage of the water in the unsaturated zone and removal by evapotranspiration were probably larger at both study sites than in karst areas.…”
Section: Recharge/discharge Relationsmentioning
confidence: 99%
“…Additionally, the unsaturated zone is thinner and probably more permeable at the Coastal Plain site than at the Piedmont site, and flow velocities in the zone probably are faster and traveltimes shorter. For comparison, faster recharge than that found at either of the sites for this study was observed throughout the year in an agricultural area underlain by a karst flow system in Pennsylvania (Gerhart, 1986;Hall, 1992b), where water percolates through sinkholes and bedrock fractures enlarged by solution weathering. Storage of the water in the unsaturated zone and removal by evapotranspiration were probably larger at both study sites than in karst areas.…”
Section: Recharge/discharge Relationsmentioning
confidence: 99%
“…A number of studies (Swamee and Ojha, 1997) attempted to simplify the existing solutions, but the resulting equations are still too complicated for routine applications in recharge basin design and require an iterative solution. The water-table fluctuation (WTF) method has been used in various studies (Gerhart, 1986;Hall and Risser, 1993), and is found to be best applied over short time periods in regions having shallow water-tables that display sharp rises and declines in water levels. The present study employs the theories of distribution of mound rise obtained from the WTF method and groundwater volume balance residual by Darcy law (Bear, 1979) in the aquifer system.…”
Section: Introductionmentioning
confidence: 99%
“…The beds of shaly limestone, shales, and sandy limestones in the Conococheague Formation (Grimsley, 1916, p. 287) tend to be less permeable than limestone and may cause the mounds in the Conococheague Formation. BEEKMANTOWN LIMESTON 197019711972197319741975197619771978197919801982198319841985198619871989 Figure 6.--Noon daily water levels at well 20-5-7 at Martinsburg, West Virginia, showing seasonal fluctuations and approximate water levels at time water-quality samples were collected. …”
Section: Ground-water Levelsmentioning
confidence: 99%